Diagnosis of a complex chromosomal rearrangement using fluorescent in situ hybridisation. Issue 9 (September 1996) - Wallerstein, R; Gibas, L; Anderson, C E; Jackson, L
Abstract : We report the use of fluorescent in situ hybridisation (FISH) to clarify a complex chromosomal rearrangement (CCR) carried by a woman presenting with recurrent miscarriages. CCRs are rare cytogenetic rearrangements involving three or more chromosomes, which can be difficult to interpret using routine cytogenetic studies with GTG banding. FISH was used to establish a correct interpretation of the maternal karyotype before amniocentesis in a present pregnancy.